Effect of motivational counselling on international changes of quitting smoking among heart disease patients. - Ishwar,Dilip Kumar (2018)
ABSTRACT: Introduction: Cardiovascular diseases (CVDs) kill more people than any other cause of death worldwide. Tobacco use and second-hand smoke exposure contribute to approximately 12% of all heart disease deaths. Tobacco use is the second leading cause of CVD, after high blood pressure. In context of Nepal, on an average 42 to 68 people die prematurely due to the consumption of tobacco and tobacco products and almost 25000 people die on an annual basis. This suggests that there is a need to do research on factors that will make people to motivate on tobacco smoking cessation changing their intention to quit smoking through intervention implementation especially those who are already suffering from heart disease. This study focused to measure the effect of motivational counseling on the intention change for quitting smoking among smokers suffering from heart disease in Dhanusha district of Nepal. Methods: The study design was pre-test post-test design without comparison group. The total number of sample was 121 smokers with heart disease patients. It was conducted in the private heart clinic in Dhanusha district. Participants having the complaint of heart disease and age ≥ 30 years old attending the clinic were included in the study. Fagerstorm test for nicotine dependence scale was used to collect the data on nicotine dependence and heaviness of smoking index was used for assessing heaviness of smoking. Similarly, mondor scale was used to collect data on motivation to quit smoking, and readiness to quit ladder was used to assess readiness to quit smoking among participants. The research proposal was reviewed and approved from Nepal Health Research Council. Results: Fagerstorm test for nicotine dependence (FTND) and heaviness of smoking index (HSI) were not found to be associated with most demographic and socio economic characteristics of the participants. The scores in the pre-test and post-test of FTND, HSI and mondor scale were found to be statistically significant and Mondor score posses a moderate coorleation with readiness to quit which determined the participant's intention to quit smoking. One point increment in FTND score means there was 3.3% decrement in intention to quit smoking whereas one point increment in Mondor score means there was 30.1% increment in intention to quit smoking [IQ = 1.073 - 0.33 (FTND) + 0.301 (Mondor)]. Conclusion: Motivational counseling was found effective to change the intention for quiting smoking. Nicotine dependency, heaviness of smoking and motivation to quit plays an important role in determining intention to quit smoking which further intends to individual smokers either to quit smoking or not. Thus, individual motivational counseling can increase the heart disese patients' intention to quit the smoking. Keywords: Intention, motivation, motivational counseling, nicotine dependence, quitting smoking